Parsubang as a Symbol of Religious Diversity Appreciation in Batak Culture - Ambarita, Jenri; Simanihuruk, Sudirman (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
Parsubang is a Batak tradition that originally emerged as a form of respect for individuals who did not consume pork, and has since evolved into a broader cultural practice symbolizing respect for religious and belief-based differences. This study examines the role of parsubang in fostering social harmony within the Batak community, focusing on how this traditional practice bridges religious divides between Muslims and Christians. The research employs a qualitative approach, gathering data through semi-structured interviews with community leaders, religious figures, and members of the Batak community in both rural and urban areas. Data analysis is conducted using thematic analysis, identifying key themes related to the values of tolerance, mutual respect, and social solidarity within parsubang. The findings show that while the form of parsubang has evolved in urban areas, its core values continue to play a significant role in maintaining social cohesion. Despite modern challenges, the practice remains a crucial element of Batak identity and interfaith harmony. The study concludes that preserving the essence of parsubang while adapting it to contemporary contexts can help maintain religious harmony and strengthen community bonds.